Arthroscopic meniscectomy for degenerative meniscal tears reduces knee pain but is not cost-effective in a routine health care setting: a multi-center longitudinal observational study using data from the osteoarthritis initiative. Issue 2 (February 2018) - Rongen, J.J.; Govers, T.M.; Buma, P.; Rovers, M.M.; Hannink, G.
Summary: Objectives: It is disputed whether arthroscopic meniscectomy is an (cost-) effective treatment for degenerative meniscus tears in day-to-day clinical practice. The objective of this study was to assess the cost-effectiveness of arthroscopic meniscectomy in subjects with knee osteoarthritis, in routine clinical practice, while taking into account the increased risk for future knee replacement surgery. We compared cost-effectiveness of arthroscopic meniscectomy compared to no surgery. Design: We used a state transition (Markov) simulation model to evaluate the cost-effectiveness of arthroscopic meniscectomy compared to no surgery in subjects with knee osteoarthritis (age range 45–79 years). Data used in the preparation of the current study were obtained from the Osteoarthritis Initiative (AOI) database. We applied a 9 years' time horizon (which is equal to the current OAI study follow up period), and evaluated cost-effectiveness from a societal perspective. The main outcome measure was the incremental cost-effectiveness ratio (Euros per quality adjusted life-year (QALY) gained). Results: Arthroscopic meniscectomy was associated with 8.09 (SD ± 0.07) QALYs at a cost of € 21, 345 (SD ± 841), whereas the no surgery was associated with 8.05 (SD ± 0.07) QALYs at a cost of € 16, 284 (SD ± 855). For arthroscopic meniscectomy, the incremental cost per QALY gained was € 150, 754. Conclusions: In day-to-day clinical practice, arthroscopic meniscectomy in subjects with knee osteoarthritis is associated with € 150, 754 per QALY gained, which exceeds the generally accepted willingness to pay (WTP) (range € 20, 000–€ 80, 000).